Real-Time PCR as a Prognostic Tool for Human Congenital Toxoplasmosis - Costa, Júlia Gatti Ladeia (American Society for Microbiology, 2013)
Real-time PCR (qPCR) was positive in 72/150 (48%) blood samples of newborns with congenital toxoplasmosis. Among infants with active retinochoroiditis, 68% had positive qPCR results, while positivity was 29% (P = 0.009) in the absence of ocular involvement. Positive qPCR was associated with the presence of retinochoroidal lesions, with an odds ratio of 2.8.